IMPLEMENTASI PERAN DAN WEWENANG OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN DAERAH ISTIMEWA YOGYAKARTA DALAM PENEGAKAN HUKUM DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Denny Perdana Seputri dan Nesya Artia Melly, Anisa Nurchassana Utomo (GEMA, 2015)
Indonesia is a country where the legal instrument written and unwritten law as a basis by the authorities and the community in action and deeds. Laws serve as the basis of state power and administration of power in all its forms, as well as making the law as a guarantee for the justice community. As mentioned in the Constitution of the Republic of Indonesia Year 1945, the implementation of the public service and enforcement of the law is also a unity in the framework of the implementation of the State as an effort to create good governance and efficient to provide welfare, justice and legal certainty for the community. So the supervision of services organized by the government is an important element in creating good governance that are based on peoples aspirations. In this case the Ombudsman representatives of DIY as a supervisory agency not only to supervise the performance of public service institutions but also perform law enforcement as an embodiment of the duties and functions under Act No. 37 of 2008. On the Ombudsman of the Republic of Indonesia. This article is based on the laws and regulations in accordance with the authority of the Ombudsman of the Republic of Indonesia, especially ORI DIY Representatives by SK Chairman of the Ombudsman No. 17 / ORI-SK / II / 2013 dated February 21, 2013 jurisdiction covers the territory of DIY and Ex Residency of Banyumas, Kedu and Surakarta